SEXUAL DIMORPHISM OF MINANGKABAUNES’ MAXILLARY CENTRAL INCISOR’S WIDTH: DISMORFISME SEKSUAL DARI LEBAR INSISIVUS SENTRAL MAKSILA PADA SUKU MINANGKABAU - Kasuma, Nila; Susi, Susi; Fitri, Haria; Fajrin, Fildzah Nurul (Dentika: Dental Journal, 2017)
Teeth are known as organs made up of the hardest mineral tissue that is resistant to decay and physical, thermal, mechanical, chemical or biological damage. Tooth crown dimensions are reasonably accurate predictors of genders especially to young individuals whose secondary skeletal characteristics are yet developed. This research aims to analyse the influence of genders to the width of maxillary central incisor Minangkabaunese. The study was conducted using cross-sectional method in Luhak Agam, Luhak Tanah Datar and Luhak Lima Puluh Kota, West Sumatra using simple random sampling technique to a total of 120 samples. Teeth width was measured in mesiodistal dimension with 0.01 mm calibrated sliding digital caliper. The measurement was done on a tooth mould at ⅓ incisal as the position of mesial and biggest distar. T-test independent statistic test was done to determine the relationship between the 2 variables. Sexual dimorphism was determined with Garn formula. The research shows significant difference (p=0.001) between the width of left and right central incisor in males and females. The average width of the male and female right maxillary incisor is 8.545 mm and 8.370 mm, while the left central incisor width is 8.877 mm in male and 8.283 mm in females. Sexual dimorphism on the right central incisor is 2.09% and 3.43% on the left side. The conclusion of the study is that maxillary central incisor width can distinguish different genders in the identification process.